Effect of Heat-Moisture Treatment on Structural Characteristics and Physico-chemical Properties of Corn Starch-Hydrocolloid: A review - Ajeng Ananda Putri; Riski Ayu Anggreini (Future Science, 2022)
The use of modified starch, especially from cereal sources in food products, is still very limited in Indonesia. Corn has a fairly high carbohydrate content so it is very potential to modify starch, such as using the heat moisture treatment (HMT) method. The HMT method is a physical modification method of starch, which will be able to produce starch with a moisture content of less than 35%. Several studies have stated that physical modification using HMT and/or can be combined with pectin, gum arabic, xanthan gum and guar gum can improve the physical characteristics of the resulting product. This review aims to determine the physical characteristics of corn starch treated with HMT modification with and without a combination of treatments using Arabic gum, xanthan gum, and guar gum. The results showed that the HMT treatment (100°C, 16 hours, 25%) had the lowest swelling power and solubility values compared to other samples. The HMT-Pectin treatment had a low syneresis value, as the impact it has good freeze- thaw stability compared with the others. Meanwhile, corn starch-modified by HMT with gum (gum arabic, xanthan gum, and guar gum) significantly did not change the type of crystallinity of starch.